Inventing Tradition in Thessalonica The Appropriation of the Past in 1 Thessalonians 2:14–16 - Rollens, Sarah E. 1984- (2016)
The socio-ethnic constitution of the Thessalonian ekklesia is notoriously difficult to pin down, but one consistently argued position is that the group was comprised largely of Gentiles. The only passage that presents a problem for this theory is 1 Thessalonians 2:14–16. Rather than focus on philological and theological issues to identify whether this passage is “Pauline” or not, this article treats 1 Thessalonians 2:14–16 as an “invented tradition” (à la Eric Hobsbawm and Terence Ranger) whic links the social experience of the Thessalonians to the nascent ekklesia in Judaea. Instead of acting as a mouthpiece for Paul's theology concerning Jews, the point of this passage may instead be to invent a coherent “past” for the Thessalonians, who may have had few other social features in common upon which to base their group identity. By appropriating an “already in place” framework for identity (Deuteronomistic theology) and by connecting the Thessalonians' experience to both the ekklesia in Jerusalem, as well as to past prophets, 1 Thess 2:14–16 attaches the Thessalonians to an identity that extends beyond their local group.
Keywords: Paul; trade workers; Interpolation; invented tradition; Associations; Thessalonians